2018
DOI: 10.1186/s12944-018-0850-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the independent and combined effects of omega-3 and vitamin B12 on phospholipids and phospholipase A2 as phospholipid hydrolyzing enzymes in PPA-treated rats as a model for autistic traits

Abstract: BackgroundAbnormal phospholipid metabolism is a major component of many neurodevelopmental disorders including autism. Oral administration of propionic acid (PPA) can produce behavioral abnormalities and biochemical features in rodents similar to those observed in autism and can thus be used as a model to understand impaired brain fatty acid metabolism in autism.MethodsThe present study was designed to understand alterations in phospholipid metabolism in the brain of a rodent model of autism and to explore ome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The finding of the current study is of great support to our previous work in which vitamin D, CoQ10, vitamin B12, carnitine, and bioflavonoids (as major components of bee pollen) demonstrate significant potency in ameliorating PPA-induced persistent autistic features in the rodent model [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Discussionsupporting
confidence: 88%
“…The finding of the current study is of great support to our previous work in which vitamin D, CoQ10, vitamin B12, carnitine, and bioflavonoids (as major components of bee pollen) demonstrate significant potency in ameliorating PPA-induced persistent autistic features in the rodent model [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Discussionsupporting
confidence: 88%
“…Approximately 23% of the body’s cholesterol is found in the CNS, and it is an important raw material for the growth and differentiation of neurons. Moreover, metabolic dysregulation characterized by reduced phospholipid levels in the brain and plasma has been implicated in ASD pathogenesis ( Alfawaz et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Omega -3 dose (200 mg/kg/day) for 30 days tested in Juvenile Rats (80-120g) after treated with propionic acid. Vit B12 (16.7 mg/kg/day) treated for 30 days after propionic acid and combination of Omega-3 and Vit B12 [97], [99]. They results showed that these supplementations reduce oxidative stress and combination inhibits clostridia growth they suggested taking this combination as therapeutic treatment.…”
Section: Supplements and Antioxidant Used To Ameliorate Or Prevent Th...mentioning
confidence: 95%